A treatment for substance abusing pregnant women - Yonkers, Kimberly Ann (2009)
We describe the adaptation of a manualized behavioral treatment for substance using pregnant women that includes components of motivational interviewing and cognitive therapy. In a pilot study conducted in 2006–2007, five non-behavioral health clinicians were trained to provide the treatment to 14 women. Therapy was administered concurrent with routine prenatal care at inner-city maternal health clinics in New Haven and Bridgeport, Connecticut, small urban cities in the USA. Substance use was monitored by self report, and urine and breath tests. Treatment fidelity was assessed using the Yale Adherence and Competence System. Behavioral treatment delivery in this setting is feasible and is being evaluated in a randomized, controlled, clinical trial.